Impulse buying in live streaming e-commerce: The role of social presence, social facilitation, and celebrity endorsement - Yona Rania Qonitah; Rina Suthia Hayu (Universitas Ahmad Dahlan, 2025)
The phenomenon of live shopping, which is increasingly popular among Generation Z, is driving changes in online shopping behavior. This study aims to examine how live streamers' attractive appearance and their real-time interaction impact hedonic and utilitarian attitudes, which in turn drive impulse buying. Additionally, it investigates the role of celebrity endorsements in moderating the correlation between these attitudes and the impulse buying behavior of Generation Z Shopee Live users in Indonesia. A quantitative research approach was utilized for this study, involving 349 Generation Z respondents selected through purposive sampling based on their impulse buying experiences on Shopee Live. Data analysis was conducted using structural equation model with partial least square analysis with Smart PLS version 4. The results revealed that live streamers' attractive appearance and their real-time interaction positively and significantly impact hedonic and utilitarian attitudes. Additionally, these attitudes were also found to positively and significantly affect impulse buying behavior. Interestingly, celebrity endorsements were detected to negatively moderate the relationship between hedonic attitudes and impulse buying, while positively moderating the correlation between utilitarian attitudes and impulse buying. The findings of this research provide valuable insights for e-commerce platforms and marketers in crafting effective live shopping strategies. By improving the visual attractiveness of streamers and promoting interactive communication, platforms can enhance both hedonic and utilitarian shopping experiences, thus fostering impulse purchases. In addition, the use of celebrity endorsements should be approached carefully, as their impact varies based on whether consumer motivations are pleasure-driven or practicality-driven.